Mobile app for crowdsourcing - Tan, Jesse Yin Xuan (Nanyang Technological University, 2020)
Crowdsourcing is a practice of engaging a group of people for a common goal such as problem solving, gathering new idea, or servicing. Nowadays, it was powered by new technologies, social media, and internet. Task crowdsourcing fully used the idea of this sourcing model to outsource task by distributing it to individual or organization. Amateur who contributed to the task will receive money as reward from the task owner. With this model, the efficiency of outsource a task was increased significantly. Mobile device is a device which connected people via internet. It run with mobile operating system (OS) that allow third-party app to be installed and run. The main mobile operating systems are Android and IOS. The motivation of this project is to utilize the idea of crowdsourcing and mobile device to achieve the purpose of distributing a task to public. This application was developed with Bubble.io, a visual programming platform. It is a web mobile application running with a browser but with Bubble.io plug-in, it can access to the device capabilities.